PENERAPAN MODEL BRAIN BASED LEARNING BERBANTUAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR MURID MATA PELAJARAN IPA SDN 10 KOTA BARAT - Polapa, Anggun Nur Fadilah; Meylan Saleh; Rifda Mardian; Abdul Haris Panai; Irvin Novita Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employed a Classroom Action Research (CAR) design to address the research problem of whether the Brain-Based Learning (BBL) model assisted by animated video media can improve students’ learning outcomes in science, specifically on the topic of the human respiratory system, in Grade V of SDN 10 Kota Barat. The objective of this study was to enhance students’ learning outcomes in science through the implementation of the BBL model supported by animated videos. The research was conducted in two cycles, each consisting of two meetings and involving four stages: planning, action, observation, and reflection. The research subjects comprised 23 students, including 13 males and 10 females. The results indicated that in Cycle I, only 4 out of 23 students achieved the Minimum Learning Mastery Criteria (≥ 80), representing 17.39%, while 19 students (82.61%) did not achieve mastery. After improvements were implemented in Cycle II, there was a significant increase in students’ learning outcomes, with 22 students (95.65%) achieving mastery and only 1 student (4.35%) not yet achieving mastery. Therefore, it can be concluded that the implementation of the Brain-Based Learning (BBL) model assisted by animated video media effectively improves students’ learning outcomes in science on the topic of the human respiratory system in Grade V of SDN 10 Kota Barat.